Using the TPACK Framework to Map Indonesian Secondary Science Teachers’ Experiences in Conducting Laboratory Learning during the Covid-19 Pandemic - Wahyudi, Dwi (Bioedusiana: Jurnal Pendidikan Biologi, 2022)
The Covid-19 pandemic brought some challenges to the continuity of educational activities around the world. In the Indonesian context, the government mandated the shift from face-to-face classrooms to online learning which burdened science teachers in maintaining laboratory instructions. Due to the closure of the schools, Indonesian secondary science teachers were forced to alter their methods of laboratory instruction by integrating digital technologies. Therefore, a qualitative methodology and a case study method were used to investigate the experiences of Indonesian secondary science teachers in conducting laboratory learning amid the Covid-19 outbreak. Moreover, the TPACK framework was utilised as a theoretical basis to map participants’ experiences. The data was obtained using semi-structured interviews with open-ended questions with two Indonesian secondary science teachers. The data then was analysed using a thematic analysis strategy to identify themes that emerged from the participants’ experiences. The emerging themes were choosing teaching content, teaching science concepts that require laboratory activities, using digital technology to facilitate students in conducting laboratory activities, using digital technology to assess students’ laboratory learning outcomes, and facing challenges in integrating digital technology into laboratory teaching. These experiences were mapped into a number of TPACK knowledge domains, such as CK, PK, PCK, TK, TCK, TPK, and XK, using the TPACK framework as a guide. However, no indication of TPCK was found in the participants’ experiences.